GAUGING THE ICT-BASED TEACHING READINESS OF PRESERVICE TEACHERS IN THE LIGHT OF 21ST CENTURY EDUCATION - Balajadia , Dexter M. (PEOPLE: International Journal of Social Sciences, 2015)
This triangulation study assessed pre-service teachers of their readiness to functionally utilize Information and Communication Technology (ICT) – based teaching strategies and techniques as corroborated with new graduates’ related experiences.Their knowledge in ICT-based teaching acquired from the educational technology courses in teacher education was correlated with their attitudes and perceptions toward the use of these strategies in causing functional learning, their perceived readiness, and technological practices. Subsequently, issues concerning the use of ICT-based strategies learned in college were sought from graduates of teacher education through exposition of experiences in their respective workplaces.This study ultimately revealed that the educational technology course experiences were not responsive enough to capacitate pre-service teachers to enact ICT-based strategies toward functional learning of their future students. They generally believe that their knowledge, potentials, and skills were not adequate to maximize ICT in designing and implementing curricular programs when they become full-fledged teachers despite their positive views on the benefits of ICT in teaching. New teacher-graduates, meanwhile, experienced limitations on the opportunities to use ICT in teaching due to lack of facilities and available resources to carry out their learned competencies. They also expressed restraint to innovate teaching as they were aghast of the demands of 21st century education. The need to revitalize the teacher education curriculum is, therefore, proposed that should be highly responsive in gearing up the potentials of pre-service teachers on ICT-based teaching in the light of 21st century education.